Mammogram : detection of malign tumors in women from Santa Catarina and Brazil (2016)
ABSTRACT: The purpose is to analyze the incidence rate of malignant neoplastic lesion by detection type and the proportional distribution of mammograms in women between 40 and 69 years of age from the State of Santa Catarina and from Brazil. This is a descriptive observational study of data from the Information Technology Department of the Unified Health System between 2009 and 2012 and the Brazilian Institute of Geography and Statistics. The greatest mammography coverage was in the group from 45 to 49 years, 22.2% in Brazilians and 23.1% in women from Santa Catarina. The greatest proportional distribution was 89.2% in Brazilian women between 40 and 44 years and women from Santa Catarina between 50 and 54 years. The incidence rates of malignant neoplastic breast lesion diagnosed by imaging increased in Brazil and Santa Catarina. In Brazil, in 2012, the highest detection was by palpation and, in Santa Catarina, by imaging. In conclusion, the screening is below the recommended, the higher proportional distributions of mammograms permitted a larger number of diagnoses of malignant neoplastic lesions and the application of mammograms as from the age of 40 years contributed to the diagnosis of breast cancer between the ages of 40 and 49 years.